Science Journalism, Value Judgments, and the Open Science Movement - Elliott, Kevin C. (Frontiers in Communication, 2019)
Science journalists face significant challenges as they seek to achieve the dual goals of providing balanced perspectives that consider all sides of the stories they cover and at the same time avoiding the presentation of unreliable or misleading information. This paper draws on recent scholarship in the philosophy of science that can help journalists navigate these challenges and report on scientific research in socially beneficial ways. The paper proposes that science journalists have the opportunity to contribute to the open science movement by identifying and explaining major value judgments in scientific research for members of the public. Journalists are uniquely situated to fulfill this role because they serve as gatekeepers of information for the public and because their investigative skills are ideal for uncovering value judgments. The paper illustrates how this principle can provide guidance for science journalists by examining a case study of recent journalistic reporting on possible health effects associated with cell phone radiation.